Effect of Temperature Photo Degradation of Titanium Dioxide Doped with Mg for Antibacterial Application - Al-Salih, Seenaa Wdaah Man Allh (American Journal of Biology and Natural Sciences, 2025)
Using a sol-gel process, titanium dioxide doped with Mg nanoparticles was synthesized with a temperature modification. By reducing by catalytic agent preparation of Mg-doped TiO2 for evaluation of the capacity antibacterial activity, bio-materials in nanopowder in solid-state produced interloping among the anatase surface nanoparticles after that, they served as a capping and stabilizing agent. The Mg-doped TiO2 NPs. XRD, SEM, and UV–vis methods were used to describe the samples. The temperature variation impacted the scale, shape, as well as the purity of Mg-doped TiO2 NPs According to XRD measurements, the average crystallite size dropped from 23.23nm to 20.70nm, while the energy band decreased from 3.33eV to 2.62eV based on UV–vis measurementsThe antibacterial activity of Mg-doped TiO2 NPs was investigated using growing minimum inhibitory concentration of gram-negative bacteria E. coli and Klebsiella spp, as well as gram-positive bacteria S.aureus and S.epidermidis, and the fungus Candida albicans. The zones for Mg-doped TiO2 NPs were between (12-13) 37C° when 25C° was between (11-12) mm. The zones for (Mg-doped TiO2) NPs were formed when the temperature of 40C° was between (12.5-14) mm. The findings of this investigation show that as the temperature rises, so does the ratio of degraded bacterial media.